2018
DOI: 10.1007/s00484-018-1571-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of season and climatic variables on testicular cytology, semen quality and melatonin concentrations in crossbred bucks reared under subtropical climate

Abstract: Seasonality in reproduction and effects of climatic variables on testicular cytology and semen quality in bucks reared under subtropical climatic conditions were not well understood. In the present study, using testicular cytology, semen evaluation and melatonin concentrations assessed over a period of 1 year, we report that bucks reared under subtropical climatic conditions did not show seasonality in reproduction. Climatic variables including temperature, relative humidity, temperature-humidity index (THI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…Benia et al (2018) obtained similar results in Ouled-Djellal rams. However, other authors (Barkawi et al, 2006;Gündoğan, 2007;Azawi and Ismael, 2012;Golher et al, 2018;Hedia et al, 2019) reported huge seasonal variation on spermatozoa concentration, with breeding season recording higher concentration than non-breeding season with winter yielding lesser sperm concentration (Wang et al, 2015;Kadili et al, 2019). Noteworthy, the sperm concentration from the current study was higher than that reported by (Chella et al, 2017) in Zulu rams.…”
Section: Discussioncontrasting
confidence: 63%
“…Benia et al (2018) obtained similar results in Ouled-Djellal rams. However, other authors (Barkawi et al, 2006;Gündoğan, 2007;Azawi and Ismael, 2012;Golher et al, 2018;Hedia et al, 2019) reported huge seasonal variation on spermatozoa concentration, with breeding season recording higher concentration than non-breeding season with winter yielding lesser sperm concentration (Wang et al, 2015;Kadili et al, 2019). Noteworthy, the sperm concentration from the current study was higher than that reported by (Chella et al, 2017) in Zulu rams.…”
Section: Discussioncontrasting
confidence: 63%
“…The mean(IQR) age of all participants was 26 (23-31) years old. Among the 1012 participants, 752 were from northern China, and the median (IQR) age was 27 (23)(24)(25)(26)(27)(28)(29)(30)(31) years old; 260 were from southern China, and the median (IQR) age was 24 (22)(23)(24)(25)(26)(27)(28)(29) years old. About 94% of the subjects were from Han ethnic group.…”
Section: Resultsmentioning
confidence: 99%
“…Some analysts speculate that the high temperatures may affect testicular spermatogenesis. However, the study conducted by Golher et al suggested that the sperm function parameters of crossbred bucks, which were reared in subtropical climate, did not show any difference in different seasons, which may be related to the advanced testicular temperature regulation mechanism in the body [31] . Our study did not record the seasons when volunteer donated their semen due to limited statistical conditions, but we will incorporate this factor into statistics in future studies.…”
Section: Discussionmentioning
confidence: 96%
“…While in the tropical region, since the photoperiod is almost similar throughout the year, other factors such as temperature and relative humidity probably become two significant contributors in the semen quality variation (de Castro et al, 2017). In more recent, sunshine duration, which defined as the duration of direct sunshine exposure to the land surface, also reported as one factor which could influence semen quality (Golher et al, 2018). All of these-mentioned factors should be discussed to provide in-depth knowledge of seasonal effects on semen quality.…”
Section: Introductionmentioning
confidence: 99%